Prognostic significance of excision repair cross complementation group 1 rs2298881 in patients with gastric cancer receiving platinum-based chemotherapy: A PRISMA-compliant meta-analysis. Issue 33 (20th August 2021) - Lv, Yalei; Xu, Mengyuan; Sun, Yidan; Liu, Yezhou; Zhao, Lijuan; Liu, Xuehui; Li, Zixuan; Shi, Gaiping; Jia, Jinhai; Bi, Lanfei; Ma, Ning; Zhang, Xiaolin; et al.
Abstract: Background: Gastric cancer (GC) is a strong cause of global cancer mortality. Nucleotide excision repair (NER) can modulate platinum-based chemotherapeutic efficacy by removing drug-produced DNA damage. Some studies have found a link between excision repair cross complementation group 1 (ERCC1) rs2298881, one gene in NER pathway, and response to chemotherapy. However, the results have been disputed. Methods: We conducted a meta-analysis to reevaluate the association between polymorphisms of NER gene (ERCC1 rs2298881) and the clinical outcomes in gastric cancer patients receiving platinum-based chemotherapy. Searching PubMed, Web of Science, EMBASE, Google Scholar, and China National Knowledge Infrastructure, 2 independent searchers found all pertinent literatures up to May 1, 2021. We enrolled studies according to consistent selection criteria, extracted and vitrified data. Crude odds ratios (ORs) and hazard ratios (HRs) with 95% confidence interval (CI) were applied to evaluate the effect of ERCC1 rs2298881 on patients treated by platinum-based chemotherapy. Results: By the data gathered from 6 independent studies, 1940 cases diagnosed with gastric cancer and treated with chemotherapy were included, containing 1208 Good-Responders and 732 Poor-Responders. With a comprehensive meta-analysis, we found that the patients with ERCC1 rs2298881A allele had a worse response to chemotherapy than those who with rs2298881C allele under allelic model (A vs C), with the pooled OR of 0.780 (95% CI: 0.611–0.996, P  = .046). And our analysis indicated that AA genotype was associated with unfavorable overall survival (HR = 1.540, 95% CI = 1.106–2.144, P  = .011) compared with CC genotype. Conclusions: ERCC1 rs2298881 is suggested as a marker of clinical outcome in gastric cancer patients treated by platinum-based chemotherapy.